Performance of water, ethylene glycol, engine oil conveying SWCNT-MWCNT nanoparticles over a cylindrical fin subject to magnetic field and heat generation. (2nd November 2022) - Manohar, G. R.; Venkatesh, P.; Gireesha, B. J.; Madhukesh, J. K.; Ramesh, G. K.
ABSTRACT: The purpose of this study is to investigate the substantial thermal performance of hybrid carbon nanotubes in three distinct base fluids (water, ethylene glycol, and motor oil) over a cylindrical porous fin in the presence of a magnetic field and an internal heat source. The current study has engineering and industrial applications, such as managing excess heat generated during the thermal process in microprocessors, air-cooled craft engines, air conditioning, and vehicles. To account for this, the best thermal distribution performance in three different base fluids was analysed. A Darcy law model is used to create the heat equation. The non-dimensional governing equation is solved using the Maple programme and the Runge Kutta Fehlberg technique's 4th and 5th orders. The numerical solutions found under various restrictions with three different base fluids are graphed and analysed in detail. It is noted that the magnetic constraint and internal heat generation parameters improve thermal performance, whereas convection and radiation parameters degrade it. In the presence of SWCNT-MWCNT, ethylene glycol performs better in terms of thermal distribution than water and engine oil based liquid.